Evaluasi Pembelajaran Online Mata Kuliah Pendidikan Seni Drama Menggunakan Model Project Based Learning - Intan Sari Ramdhani (Jurnal Ilmiah Wahana Pendidikan, 2021)
This study aims to describe the evaluation of the use of the Project Based Learning (PBL) model in online learning for drama courses at the Teacher Training and Education Faculty of the Indonesian Language and Literature Education Study Program at Muhammadiyah University, Tangerang. The research method used in this study is a qualitative descriptive method with steps to collect data, record data, analyze data and describe research results. The object of this research is the use of the PBL model. The results showed that 1) Drama Learning conducted online led to a student monologue performance, 2) This Project Based Learning model was very suitable to be applied in online learning for Drama Arts Education Courses at FKIP PBSI UMT, 3) The use of the Project Based Learning model was easy. implemented in Drama learning, 4) By applying Project Based Learning in drama learning, students become more active, creative and independent in producing a work, 5) The learning objectives of the Drama Arts Education course are achieved, 6) Students have monologue drama performances, 7 ) Stimulate students' competitive attitude to be able to compete in the Student Virtual Monologue Festival as UAS for Drama Arts Education courses at FKIP UMT, 8) The value of drama learning using the Project Based Learning model shows good and satisfying scores, and 9) Student responses to online learning Drama Arts Education course men use the Project Based Learning model.